EVALUATION OF THE WOMEN'S INDOOR HOCKEY ATHLETE TRAINING PROGRAM AT PON XX PAPUA IN 2021 - Silalahi, Otta Lestarina; Ibrahim, Ibrahim; Sitorus, Ingrid Margaretha (Journal of Physical Education, Health and Sports Recreation, 2023)
This research aims to determine: Context, input, process, products for female indoor hockey athletes at XX Papua PON 2021. The type of research is descriptive qualitative with a cyclical research design. The subjects in this research were 1) administrators; 2) trainer; 3) 10 athletes taking part in XX Papua PON 2021. The instruments used in this research were observation sheets and interviews. The research results obtained in this study obtained good results and all stages ran smoothly.